The Development of Preference for or Against Choice-making Opportunities - (:unkn) unknown (My University, 2017)
ABSTRACT THE DEVELOPMENT OF PREFERENCE FOR OR AGAINST CHOICE-MAKING OPPORTUNITIES by Melissa A. Drifke The University of Wisconsin-Milwaukee, 2017 Under the Supervision of Professor Jeffrey Tiger Many individuals prefer contexts in which choice-making opportunities are available relative to contexts in which the same experiences are arranged without the opportunity to choose. Further, providing contingent access to choice-making opportunities often results in increased engagement and decreased problem behavior for individuals in reinforcement-based programs. Little is known about why preferences for choice-making contexts develop. The current study examines pairing choice-making contexts with increased or decreased reinforcer magnitude, quality, and immediacy to develop preference for choice-making or no-choice contexts. We examined preferences in concurrent chains arrangements consisting of selection responses, brief work requirements, and reinforcement. In choice conditions, the child selected their edible item; in no-choice conditions, a single edible was available. During baseline probes, the edible items were identical, but during conditioning, edibles differed in magnitude, quality, or immediacy. Using these conditioning histories, we created changes in preference in 100% of opportunities, extending previous literature in this area. Keywords: preference, choice, magnitude, quality, immediacy
Keywords: Aba; Choice; Conditioning; Preference